Lingwistyczna charakterystyka kontraktu jako gatunku na przykładzie mowy propinacyjnej z XIX wieku - Kuć, Joanna (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2018)
The article is an attempt of a genre analysis of the nineteenth-century sale alcohol agreement as a contract. This is a special document, because this type of act was written only once (L-140) on 412 analyzed contracts. The genre scheme of the old contract is possible to compare it with other nineteenth-century contracts. Although not easy to describe because of the typological confusion and not always the unambiguous genre signals (contract / intermediary declaration / sale alcohol agreement), they are similar to modern notarial contracts of this type. The basic registers of quality features of a nineteenth-century contract are: a clear functional intention, a coherent, formalized structure, a monolithic, specific dialogue between the sender and the receiver, the sender’s autocreation as an expert in legal action serves to build the impression of a contract involving two parties. At the source of the contract lies one of the basic speech acts: a declaration that evokes agreement, used in many social and communication situations.